A Study of Job Insecurity and Turnover Intentions Among Bullied Employees in Pakistan - Does Psychological Capital Ameliorate? - Fatima Ashraf; Muhammad Asif Khan (National University of Modern Languages (NUML), Islamabad, 2022)
This study aimed at investigating whether job insecurity and turnover intentions are outcomes of workplace bullying, and whether psychological capital is a moderator of relationships of workplace bullying with job insecurity and with turnover intentions among telecom, banking and healthcare sectors in Pakistan. Employing snowball sampling method, we drew a sample of 300 respondents from various firms of Pakistan using a cross-section study design. Study instruments included the Negative Acts Questionnaire, (Einarsen et al., 2009) the Psychological Capital Questionnaire, (Luthans et al., 2007) the Job Insecurity Scale, (Ashford et al., 1989) and three items each from Singh et al. (1996) and Camman et al. (1979) quitting intentions scales. Data were analysed using correlation, regression, and moderation techniques. Results showed that workplace bullying prompts job insecurity and quitting intentions in bullied employees and psychological capital acts as an important resource by offering a buffering mechanism that offsets the undesirable impact of workplace bullying on job insecurity and quitting intentions. This study mainly highlights the instrumentality of psychological capital as a positive psychological resource to the negative impact of work-place bullying on job insecurity and quitting intentions. This study makes a novel contribution to literature by testing for buffering effect of psychological capital within bullying prone work contexts in Pakistan, and offers psychological capital as a preemptive individual-level coping mechanism bullying-prone work settings.